Трофеї половецького вождя з Чунгульського кургану: переужиток, ритуальні функції та символіка - Галенко, О.; Рассамакін, Ю.; Вудфін, В.; Голод, Р. (Археологія, 2016)
У статті розглядається поховання степового ватажка, найімовірніше половецького князя із Чунгульского кургану, більшість виявлених предметів якого були воєнними трофеями. Робиться спроба встановити зміст деяких предметів та на підставі порівняльного матеріалу визначити їх походження. This article interprets as trophies many of the grave goods excavated from the burial of a steppe leader — likely a Polovtsian ‘prince’ — within the Chungul Kurgan in southern Ukraine. The current study focuses on three kinds of objects: those embellishing horses, embroideries on vestments, and belts. Written sources about the culture of the Eurasian steppe of the 11th—13th centuries CE, comparative study of items in European collections, and the archaeological details of the exact manner of deposition have allowed reconstructions of the meanings of these finds in daily life. Moreover, it is now possible to propose their distinctive role in the burial ritual. Two items found among the horse trappings can be shown to have originated as disassembled parts of objects made in northwest Europe for Christian ritual use. A similar re-purposing can be observed in the embroidery on one of the caftans. Originally embroidered as part of church furnishings, a fragmentary Deesis scene showing an archangel with a donor figure was attached to a caftan — cutting off the hands of the donor — and was rearranged into a new composition that presented the originally secondary winged figure as a victory or a Turkic divinity. Finally, three of the five belts found in the burial can be definitively attributed to northwestern European production. Their dispositions on and around the body allow them to be interpreted as symbols of Turkic charisma in their new location. The electrum belt around the neck, likely of Anatolian manufacture, marks the submission of the deceased before the divinities and spirits of the Turkic afterlife. The grave goods discussed here, as well as the total burial inventory, allow us to propose a possible identity for the deceased. He could likely have been a Polovtsian leader allied to the Bulgarian tsar Kaloyan. The joined Polovtsian and Bulgarian forces defeated the Crusader army at Adrianople in 1205 and led Baldwin I of Flanders, first Emperor of Constantinople, into captivity. В погребении степного предводителя, вероятно, половецкого князя, в Чунгульськом кургане значительную часть предметов можно относить к военным трофеям. Целью данной статьи является выяснение смысла использования для некоторых из них — двух украшений конской уздечки, фрагмент кафтана с изображениями Архангела и ктитора, а также пяти поясов. С этой целью, на основании сравнительного анализа, было установлено их происхождение. Привлекая письменные источники о культуре степной Евразии ХІ—ХІІІ вв., сравнительные вещи в европейских коллекциях, а также данные раскопок о положении этих вещей по отношению к умершему и манипуляции с ними, дается оценка способа использования данных предметов в быту, а также их символическое значение в погребальном обряде. Украшения узды коня оказались деталями сакральных христианских изделий. Обе вещи происходят с СевероЗападной Европы рубежа ХІІ—ХІІІ вв. Текстильный фрагмент с золотной вышивкой сохранил линию обрезания, которая проходила по фигуре ктитора так, что его ладони были обрезаны. Фрагмент был частью церковного покрывала со сценой Деисуса. Приоритетной для половцев в сцене Деисуса была фигура крылатого Архангела. Из пяти поясов, находившихся при умершем, три происходили из Северо-Западной Европы ХІІ — начала ХІІІ в. Согласно степной моде, пояса традиционно относились к самым важным символам достоинства и харизмы. Положение пояса из электрума на шее умершего символизировало смирение перед богами и духами потустороннего мира. Эти, а также другие находки из погребения, дают возможность видеть в погребенном предводителя половцев, союзников болгарского царя Калояна, которые разгромили войска крестоносцев во главе с первым латинским императором Константинополя Болдуином І, бывшим графом фландрским, в битве при Адрианополе в 1205 г.